Larangan Memainkan Talempong saat Padi Mulai Berbuah: Kearifan Lokal Masyarakat Unggan, Sumpur Kudus - Purwantono, Purwantono; Masriadi, Masriadi; Putri, Rahmaida; Rivaldi, Thio; Indrata, Syahyuli (Al-DYAS, 2026)
The tradition of prohibiting the playing of talempong when rice plants are bearing grain is a form of local wisdom that continues to be maintained by the community of Nagari Unggan, Sumpur Kudus Subdistrict, Sijunjung Regency, and is believed to be associated with belief in orang bunian, who are thought to cause the rice to become ampo (empty grain) if talempong is played during critical growth phases. This study aimed to describe this tradition and analyse the social, spiritual, and ecological meanings embedded within it. A descriptive qualitative approach was employed, with data collected through participatory observation, in-depth interviews, and documentation during the Kuliah Kerja Nyata (KKN) community service program conducted from 17 June to 17 July 2025 in Nagari Unggan. Data were analysed using the Miles and Huberman model to organise, reduce, and present the findings systematically. The results show that the prohibition on playing talempong functions as a mechanism of social control, a form of respect for nature and ancestors, and an effort to protect rice crops during critical growth stages. This tradition also contains educational value for younger generations and remains relevant to be preserved amidst modernisation as part of strengthening local cultural identity and the community’s ecological ethics.